2015
DOI: 10.1002/cbic.201500217
|View full text |Cite
|
Sign up to set email alerts
|

Structural Integrity of the A147T Polymorph of Mammalian TSPO

Abstract: Ligands of the transmembrane protein TSPO are used for imaging of brain inflammation, but a common polymorphism in TSPO complicates their application to humans. Here we determined the three-dimensional structure and side chain dynamics of the A147T polymorph of mammalian TSPO in complex with the first-generation ligand PK11195. We show that A147T TSPO is able to retain the same structural and dynamic profile of the wild-type protein and thus binds PK11195 with comparable affinity. Our study is important for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 42 publications
2
44
0
Order By: Relevance
“…Twom ajor ligand-binding sites in the structure of mammalian TSPO have hitherto been identified. The binding site observed in the 3D structure of the mTSPO/(R)-PK11195 complex [18,23] is common to severalr adioligands according to competition experiments. [27] The second binding site is also located neart he cytosolic side of the membrane and is formed by residues 147-159 in transmembrane region five.…”
Section: Discussionmentioning
confidence: 99%
“…Twom ajor ligand-binding sites in the structure of mammalian TSPO have hitherto been identified. The binding site observed in the 3D structure of the mTSPO/(R)-PK11195 complex [18,23] is common to severalr adioligands according to competition experiments. [27] The second binding site is also located neart he cytosolic side of the membrane and is formed by residues 147-159 in transmembrane region five.…”
Section: Discussionmentioning
confidence: 99%
“…Jaremko and colleagues have argued that the differences arise from crystal packing effects. 44,48 However, the published crystal structures were determined from at least five different crystal forms, each with unique differing packing arrangements and intermolecular contacts, yet all yield the same overall tertiary structure. Thus, it is unlikely that “crystal packing” is the cause of these major discrepancies.…”
Section: Crystal and Nmr Structures: Similarities And Differencesmentioning
confidence: 99%
“…An 18 kDa translocator protein (TSPO) polymorphism explains differences in binding affinity of the PET radioligand PBR28. It has been suggested that in the cases of PBR28 and other second-generation ligands, A147T mTSPO might no longer be able to retain the same structural and dynamic profile as the wild-type protein and thus binds these ligands with lower affinity [ 66 ]. Nonetheless, this polymorphism does not affect affinity for PK 11195 [ 67 ].…”
Section: Tetrapyrroles Including Protoporphyrins Such As Ppix Asmentioning
confidence: 99%